Skip to main content
Chemistry LibreTexts

General formulation of Distribution Functions

  • Page ID
    5245
  • [ "article:topic", "Author tag:Tuckerman", "showtoc:no" ]

    Recall the expression for the configurational partition function:

    \[Z_N = \int d{\textbf r}_1\cdots d{\textbf r}_N e^{-\beta U(r_1,...,r_N)}\]

    Suppose that the potential \(U\) can be written as a sum of two contributions

    \[U({{\textbf r}_1,...,{\textbf r}_N}) = U_0({{\textbf r}_1,...,{\textbf r}_N}) + U_1({{\textbf r}_1,...,{\textbf r}_N})\]

    where \(U_1\) is, in some sense, small compared to \(U_0\). An extra bonus can be had if the partition function for \(U_0\) can be evaluated analytically.

    Let

    \[ Z_N{^{(0)}}= \int {d{\textbf r}_1\cdots d{\textbf r}_N}e^{-\beta U_0({r_1,...,r_N})}\]

    Then, we may express \(Z_N\) as

    \[Z_N=  {Z_N{^{(0)}}\over Z_N{^{(0)}}}\int d{\textbf r}_1\cdots d{\textbf r}_Ne^{-\beta U_0(r_1,...,r_N)}e^{-\beta U_1(r_1,...,r_N)}\]

    \[ = Z_N{^{(0)}}\langle e^{-\beta U_1(r_1,...,r_N)}\rangle_0\]

    where \(\langle \cdots \rangle _0 \) means average with respect to \(U_0\) only. If \(U_1\) is small, then the average can be expanded in powers of \(U_1\):

    \[ \langle e^{-\beta U_1}\rangle_0 = \underline { 1 - \beta \langle U_1\rangle_0 +{\beta^2 \over 2!} \langle U_1^2 \rangle_0 - {\beta^3 \over 3!}\langle U_1^3 \rangle_0 +\cdots}\]

    \[  =\underline { \sum_{k=0}^{\infty} {(-\beta)^k \over k!}\langle U_1^k \rangle_0}\]

    The free energy is given by

    \[ A(N,V,T) = -{1 \over \beta}\ln \left({Z_N \over N!\lambda^{3N}}\right) = -{1 \over \beta}\ln \left({Z_N^{(0)} \over N!\lambda^{3N}}\right)-- {1 \over \beta}\ln \langle e^{-\beta U_1}\rangle_0\]

    Separating \(A\) into two contributions, we have

    \[ A(N,V,T) = A{^{(0)}}(N,V,T) + A{^{(1)}}(N,V,T)\]

    where \(A^{(0)} \) is independent of \(U_1\) and is given by

    \[ A{^{(0)}}(N,V,T) = -{1 \over \beta}\ln \left({Z_N{^{(0)}}\over N!\lambda^{3N}}\right)\]

    and

     

    \( A{^{(1)}}(N,V,T)\)

    $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \( -{1 \over \beta}\ln \langle e^{-\beta U_1}\rangle_0\)

     
      $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \(-{1 \over \beta}\ln \langle \sum_{k=0}^{\infty}{(-\beta)^k \over k!}\langle U_1^k \rangle_0 \)

     


    We wish to develop an expansion for \(A^{(1)}\) of the general form

    \[A{^{(1)}}= \sum_{k=1}^{\infty} {(-\beta)^{k-1} \over k!}\omega_k\]

    where \(\underline {\omega _k}\) are a set of expansion coefficients that are determined by the condition that such an expansion be consistent with \(\ln\langle \sum_{k=0}^{\infty} (-\beta)^k \langle U_1^k\rangle_0 /k!\).

    Using the fact that

    \[\ln(1+x) = \sum_{k=1}^{\infty} (-1)^{k-1} {x^k \over k}\]


    we have that

     

    \( -{1 \over \beta}\ln \left(\sum_{k=0}^{\infty}{(-\beta)^k \over k!} \langle U_1^k \rangle_0\right)\)

    $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \( -{1 \over \beta}\ln \left(1 + \sum_{k=0}^{\infty}{(-\beta)^k \over k!} \langle U_1^k \rangle_0\right)\)

     
           
      $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \(\underline { -{1 \over \beta}\sum_{k=1}^{\infty}(-1)^{k-1}{1 \over k}\left(\sum_{l=1}^{\infty}{(-\beta)^l \over l!}\langle U_1^l\rangle_0\right)^k } \)

     


    Equating this expansion to the proposed expansion for \(A^{(1)} \), we obtain

    \[\sum_{k=1}^{\infty}(-1)^{k-1}{1 \over k}\left(\sum_{l=1}^{\infty} {(-\beta)^l \over l!} \langle U^l_1 \rangle _0\right)^k = \sum_{k=1}^{\infty} (-\beta)^k {\omega_k \over k!}\]
    This must be solved for each of the undetermined parameters \(\underline {\omega_k} \), which can be done by equating like powers of \(\beta \) on both sides of the equation. Thus, from the \(\beta ^1 \) term, we find, from the right side:

    \[{\rm Right\ Side}:\;\;\;-{\beta \omega_1 \over 1!}\]


    and from the left side, the \(j = 1\) and \(k = 1 \) term contributes:

    \[{\rm Left\ Side}:\;\;\;-{\beta \langle U_1 \rangle_0 \over 1!}\]


    from which it can be easily seen that

    \[\omega_1 = \langle U_1 \rangle_0\]


    Likewise, from the \(\beta ^2 \) term,

    \[ {\rm Right\ Side}:\;\;\; {\beta^2 \over 2!}\omega_2\]


    and from the left side, we see that the \(l = 1, k = 2 \) and \(l = 2, k = 1\) terms contribute:

    \[{\rm Left\ Side}:\;\;\; {\beta^2 \over 2}\left(\langle U_1^2 \rangle_0- \langle U_1 \rangle_0^2\right)\]


    Thus,

    \[ \omega_2 = \langle U_1^2 \rangle_0 -\langle U_1\rangle_0^2\]


    For \(\beta ^3\), the right sides gives:

    \[ {\rm Right\ Side}:\;\;\; -{\beta^3 \over 3!}\omega_3\]


    the left side contributes the \(l = 1, k = 3, k = 2, l = 2 \) and \(l = 3, k = 1 \) terms:

    \[ {\rm Left\ Side}: -{\beta^3 \over 6}\langle U_1^3 \rangle + (-1)^2 {1 \over 3}(-\beta \langle U_1\rangle _0 )^3 - {1 \over 2} \left ( -\beta \langle U_1 \rangle _0 + {1 \over 2}\beta^2\langle U_1^2 \rangle\right)^2\]


    Thus,

    \[\omega_3 = \langle U_1^3 \rangle_0 + 2\langle U_1 \rangle_0^3- 3\langle U_1 \rangle_0\langle U_1^2 \rangle_0\]

     

    Now, the free energy, up to the third order term is given by

    \(A\) $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \(\underline { A{^{(0)}}+ \omega_1 - {\beta \over 2}\omega_2 + {\beta^2 \over 6}\omega_3 \cdots} \)

     
           
      $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \( -{1 \over \beta}\ln \left({Z_N{^{(0)}}\over N! \lambda^{3N}}\right) + \langle U_1 \rangle_0 - {\beta \over 2} \left \langle U_1^2 \rangle_0 - \langle U_1\rangle _0^2 \right ) + {\beta^2 \over 6} \left (\langle U_1^3 \rangle - 3 \langle U_1 \rangle _0\langle U_1^2 \rangle_0 + 2\langle U_1 \rangle_0^3 \right)+ \cdots\)

     

     

    In order to evaluate \(\langle U_1 \rangle _0 \), suppose that \(U_1\) is given by a pair potential

    \[U_1({{\bf r}_1,...,{\bf r}_N}) = {1 \over 2}\sum_{i\neq j}u_1(\vert{\bf r}_i - {\bf r}_j\vert)\]


    Then,

     

    \(\langle U_1 \rangle_0\) $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \( {1 \over Z_N{^{(0)}}}\int {d{\textbf r}_1\cdots d{\textbf r}_N}{1 \over 2} \sum_{i \ne j} u_1(\vert{\textbf r}_i-{\textbf r}_j\vert)e^{-\beta U_0( r_1,...,r_N)}\)

     
           
      $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \(\underline { {N(N-1) \over 2 Z_N{^{(0)}}}\int d{\textbf r}_1 d{text\bf r}_2 u_1(\vert r_1 - r_2 \vert)\int d{\textbf r}_3\cdots d{\textbf r}_Ne^{-\beta U_0({{\bf r}_1,...,{\bf r}_N})} }\)

     
           
      $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \(\underline { {N^2 \over 2V^2}\int d{\textbf r}_1 d{\textbf r}_2 u_1(\vert {\textbf r}_1-{\textbf r}_2\vert) g_0^{(2)}({\textbf r}_1,{\textbf r}_2)}\)

     
           
      $\textstyle =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$ data-cke-saved-style =$

    \(\underline { {\rho^2 V \over 2}\int_0^{\infty}4\pi r^2 u_1(r)g_0(r)dr }\)

     


    The free energy is therefore given by

    \[ A(N,V,T) = -{1 \over \beta}\ln\left({Z_N^{(0)} \over N! \lambda ^{3N} } \right ) + {1 \over 2} \rho ^2 V \int _0^{\infty} 4 \pi r^2 u_1 (r) g_0 (r) dr - {\beta \over 2} \left ( \langle U_1^2 \rangle_0 - \langle U_1 \rangle_0^2\right)\cdots \]